2011
DOI: 10.1158/1535-7163.mct-10-0630
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Fractionated Radiation Potentiates the Effects of Cisplatin Independent of the Hyper-Radiation Sensitivity in Human Lung Cancer Cells

Abstract: In this study, the role of hyper-radiation sensitivity (HRS) in potentiating the effects of cisplatin by low-dose fractionated radiation (LDFRT) was evaluated in four human non-small cell lung cancer cell lines. Presence of HRS and cisplatin enhancement ratio (CER) by LDFRT/2 Gy was assessed using colony-forming and apoptotic assays. Cell-cycle disturbances were studied by flow cytometry. Expression of genes involved in apoptosis was assessed using real-time reverse transcriptase PCR arrays. H-157 cells showed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
5
44
0
Order By: Relevance
“…The mechanisms underlying HRS are still not completely understood but are associated with a failure to arrest in early G 2 and increased apoptosis (26, 27). Nonetheless, it has been suggested that mechanisms other than a failure to arrest in early G 2 can lead to HRS since some cells lacking the capacity to arrest in G 2 after LDFRT are also negative for HRS (28). In an effort to identify biomarkers for HRS and improve our current understanding of chemopotentiation by LDFRT we analyzed different cellular pathways after exposure to a combined regimen of mDCF and LDFRT.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying HRS are still not completely understood but are associated with a failure to arrest in early G 2 and increased apoptosis (26, 27). Nonetheless, it has been suggested that mechanisms other than a failure to arrest in early G 2 can lead to HRS since some cells lacking the capacity to arrest in G 2 after LDFRT are also negative for HRS (28). In an effort to identify biomarkers for HRS and improve our current understanding of chemopotentiation by LDFRT we analyzed different cellular pathways after exposure to a combined regimen of mDCF and LDFRT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HRS failed to induce prosurvival transcription factors, that are necessary for increasing the levels of MDR-1 gene [53]. Hence, no MDR-1 induction in response to LD-FRT will help to increase the effects of chemotherapy, that is often mitigated by MDR-1 [54]. The use of LD-FRT with chemotherapy provides a new strategy to improve tumor downstaging through the use of radiotherapy as a biological modifier of the chemotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose fractionated radiotherapy (LD-FRT), in particular, has been demonstrated to enhance the effectiveness of multiple chemotherapeutic agents, including carboplatin, cisplatin, docetaxel, etoposide, gemcitabine, and paclitaxel, in a variety of tumor cell lines (24)(25)(26)(27). Preliminary results of clinical trials combining LD-FRT with chemotherapy have shown that this treatment can be both feasible and effective (28,29).…”
Section: Introductionmentioning
confidence: 99%